2005
DOI: 10.1161/01.atv.0000170130.85334.38
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral Cytomegalovirus Inducible Gene 5/Viperin Is Expressed in Atherosclerosis and Regulated by Proinflammatory Agents

Abstract: Objective-Inflammatory processes play an important role in atherosclerosis, and increasing evidence implies that microbial pathogens and proinflammatory cytokines are involved in the development and activation of atherosclerotic lesions. To find new inflammatory genes, we explored the vascular transcriptional response to an activator of innate immunity bacterial lipopolysaccharides (LPSs). Methods and Results-Gene

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 18 publications
4
48
0
Order By: Relevance
“…1,2 In the following studies using oligonucleotide microarray chip assays, viperin has been recognized as a highly inducible candidate gene in response to a wide range of viruses and microbial products such as LPS and double-stranded RNA, 3,4 implying that viperin is an important component of innate immunity to diverse pathogens. Viperin induction upon stimulation has been reported in human fetal astrocytes, 5 fibroblasts, Huh-7 and HepG2 cells 6,7 in vitro, and in disease conditions such as vascular cells of atherosclerosis 8 and liver tissue of patients with chronic hepatitis C. 3 Nevertheless, the cell types that are capable of producing viperin are still enigmatic, and the functions of viperin other than its antiviral activity have remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In the following studies using oligonucleotide microarray chip assays, viperin has been recognized as a highly inducible candidate gene in response to a wide range of viruses and microbial products such as LPS and double-stranded RNA, 3,4 implying that viperin is an important component of innate immunity to diverse pathogens. Viperin induction upon stimulation has been reported in human fetal astrocytes, 5 fibroblasts, Huh-7 and HepG2 cells 6,7 in vitro, and in disease conditions such as vascular cells of atherosclerosis 8 and liver tissue of patients with chronic hepatitis C. 3 Nevertheless, the cell types that are capable of producing viperin are still enigmatic, and the functions of viperin other than its antiviral activity have remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies showed that viperin is induced in various cell types by IFN-α and IFN-β, associates with the cytosolic face of the endoplasmic reticulum (ER), and inhibits human cytomegalovirus replication when preexpressed in human fibroblasts (8). Since then, viperin has been shown to be induced by several factors, including lipopolysaccharide (10)(11)(12), and to inhibit a broad range of viruses, including HIV-1 (13), West Nile virus (14), hepatitis C virus (15,16), dengue virus type 2 (17), influenza A virus (18), and tick-borne encephalitis virus (19). Gene-profiling microarray studies have shown that the viperin gene is one of the most highly inducible ISGs upon infection with a wide range of RNA viruses (20).…”
mentioning
confidence: 99%
“…Viperin was then found to be induced by both type I and type II IFN and to exhibit antiviral activity against HCMV (9). Furthermore, the results of several gene-profiling microarray studies showed that the viperin gene is one of those that is highly induced by a range of different viruses (20,25,38,40,42,46) and microbial products, such as lipopolysaccharide (35,42), the double-stranded RNA analog poly(I-C) (39), and double-stranded B-form DNA (22), in various cell types.The human viperin gene encodes a protein of 361 amino acids with a predicted molecular mass of 42.2 kDa. Protein sequence analysis reveals a CX 3 CX 2 C motif, which is found in the superfamily of S-adenosyl methionine (SAM)-dependent radical enzymes (44) in residues 83 to 90 of human viperin.…”
mentioning
confidence: 99%